Photosulfoxidation Catalysis as the Driving Principle for Deazaoxaflavin Photoredox Catalyst Formation - Křížová, Karolína; Ismail, Rimeh; Nguyen, Tung Anh; Bříza, Marek; Geleverya, Anna O; Ciotta, Chiara; Guerra, Valentino L P; Kovaříček, Petr (The Journal of organic chemistry, 2025)
Catalysts are essential for sustainability because they decrease energy and resource consumption in the production of high value-added products. The design of a novel catalyst is a challenging and expensive target, and a simplified methodology for catalyst development can trigger burgeoning progress in both academic and applied research. Here, we demonstrate a reaction network that autonomously yields the photoredox catalyst for the transformation of the provided substrate under applied catalytic conditions. The system stems from the reversible condensation pathway leading to deazaoxaflavins, 2H-chromeno[2,3-d]pyrimidine synthetic analogs of flavins, with which they share photoorganocatalytic activity. We report on the photocatalytic activity of deazaoxaflavins and their covalent dynamic behavior. The reversibility principle allows for the exchange of one of the deazaoxaflavin constituents for a different moiety, thus leading to adaptability of the catalyst. We argue that the observed phenomenon is of thermodynamic origin and thus can be applied to other photo/organocatalytic reactions in which the combination of a suitable substrate and conditions is the governing principle for catalyst formation.